Maintaining the Integrity of Democratic Principles with Congressional Remedies: An Assessment of Petitioning for Rulemaking under the Endangered Species Act. (4th March 2021) - Henschen, Beth; McLauchlan, William P.
Abstract : An important objective of the 1946 Administrative Procedure Act (APA) was to maintain the integrity of democratic principles in the federal bureaucracy. A provision in the APA stipulating that agencies give interested persons the right to petition for the issuance, amendment, or repeal of a rule democratizes the agenda setting process of regulatory agencies, setting a minimum for participatory opportunities. In the Endangered Species Act (ESA), administered by the Fish and Wildlife Service (FWS), Congress used statutory remedies to underscore the democratic objectives of the APA. In addition to providing a fairly broad petition process in the ESA, Congress set deadlines by which the FWS would act on petitions for rulemaking, and also allowed any person to enforce the deadlines by initiating a civil suit against the agency. Using an original data set of agency responses over a 12-year period to 127 petitions for listing and delisting fauna, this study assesses whether the earliest stage of agenda setting in the FWS furthers the commitment to democratic principles such as accountability, responsiveness, and responsibility. Consideration is also given to various alternatives Congress may choose to employ to maintain the integrity of these principles in administrative agencies.